‘Prophet Ibrahim’s faith and interfaith dialogue: a philosophical inquiry into religious epistemology’. - Md. Delwar Husen (Cogent Arts & Humanities)
The narrative of the Prophet Ibrahim’s (A.S.) spiritual quest in search of his Lord within the Qur’an sows the seeds of a philosophical investigation. This research is a qualitative study with a literature review approach, using primary and secondary data sources and content analysis as a data analysis technique. The objective of this article is to illustrate Prophet Ibrahim’s faith and interfaith dialogue and his philosophical quest to seek the Lord on the basis of Islamic epistemology. While traditional studies focus on his theological and historical relevance, this inquiry uniquely explores his faith as an epistemological process that integrates both divine revelation and rational engagement with the world. Meanwhile, this research contributes to contemporary debates in religious epistemology by addressing conventional dichotomies between belief and reason, asserting that religious knowledge is a dynamic and dialogical process. The outcomes of this study demonstrate the philosophical basis of Prophet Ibrahim’s beliefs in God, which includes the approach model of constructive critical thinking and transformative pedagogy as a system of education.